Fictional portrayals of Spain's transition to democracy : transitional fantasies - Walsh, Anne L. (Cambridge Scholars Publishing, 2017)
This manuscript looks at a selection of narratives published in Spain during the transition to democracy and compares them with more recent publications. The main focus here is how fiction brings an extra dimension to the recreation of the past, by adding imagination to historical fact. One effect of this is to challenge readers or spectators to question the effect the reliability of the narrator has on conviction about the events told. By using a specific moment in time, Spain's Transition, it will be seen that memory, history and imagination all blend together to create very different storie.